1991
DOI: 10.1142/s0217751x91001611
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative Approaches to Determining the Behavior of the Gluon Propagator and Quark Propagator in Quantum Chromodynamics by Schwinger-Dyson Equations

Abstract: The attempts to describe the behavior of the gluon propagator and quark propagator by using truncated Schwinger-Dyson equations and Slavnov-Taylor identities are reviewed. Special attention is paid to the problem of infrared behavior of Green’s functions. The most important attempts to calculate the gluon propagator using the axial as well as the covariant gauge are critically discussed. Furthermore, an approach concerning the gluon propagator is presented, with the background-field method as its basis. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…[See also, Hädicke (1991).] This is important because in the application of DSEs to hadronic physics a physically reasonable form for the quark propagator is needed and, in practice, this is obtained by solving the quark DSE with Ansätze for the gluon propagator and quark-gluon vertex, with the former often being motivated by studies of the DSE for the gluon propagator.…”
Section: Gauge Boson Sector Of Qcdmentioning
confidence: 99%
See 1 more Smart Citation
“…[See also, Hädicke (1991).] This is important because in the application of DSEs to hadronic physics a physically reasonable form for the quark propagator is needed and, in practice, this is obtained by solving the quark DSE with Ansätze for the gluon propagator and quark-gluon vertex, with the former often being motivated by studies of the DSE for the gluon propagator.…”
Section: Gauge Boson Sector Of Qcdmentioning
confidence: 99%
“…The pragmatic benefit of Eq. (6.43) is again obvious: we are confronted with differential equations instead of integral equations [e.g., Roberts and McKellar (1990), Haeri andHaeri (1991), Williams et al (1991), Hawes and Williams (1991), Hädicke (1991)]. Hence we can obtain solutions for both spacelike and timelike momenta, which enables a study of the singularity structure of the quark propagator.…”
Section: Quark Confinementmentioning
confidence: 99%
“…This manifestly relativistically covariant approach, recent reviews of which can be found in Refs. [2,3], has provided the foundation for a useful and successful understanding of the phenomena of low-energy QCD by facilitating the construction of realistic field-theoretic models [4].…”
Section: Introductionmentioning
confidence: 99%
“…we consider eq. (10) with the model kernel of the form (13). The parameters of the model are presented in Table I.…”
Section: Numerical Results For Iteration Methodsmentioning
confidence: 99%